Visual Rhetoric Analysis of “A Photo of a COVID-19 Victim in Indonesia Trigger Fear and Denial” by Joshua Irwandi - Rudhyni, Moch. Rizky Satrio (Universitas Ciputra, 2022)
Photojournalism by Joshua Irwandi uploaded on social media Instagram caused various responses among netizens. The photo showed the figure of a human body which was the corpse of a person who died from Covid-19 placed on a bed. This figure looked stiff and was wrapped in a shroud with plastic coated all over their body. The purpose of this research is to find out the visual rhetoric and elements of message arrangement in Joshua Irwandi’s photo work. This research uses a qualitative approach with Sonja K. Foss’ visual rhetoric analysis. The results of the analysis show that persuasive visual rhetoric will have an effect on the audience, if the visual symbols presented are familiar and close to the audience and are currently happening. Keywords: Visual rhetoric, photography, Joshua Irwandi, Covid-19